A single dose of epidermicin NI01 is sufficient to eradicate MRSA from the nares of cotton rats. (13th December 2016) - Halliwell, Samantha; Warn, Peter; Sattar, Abdul; Derrick, Jeremy P.; Upton, Mathew
Abstract : Objectives: To investigate the efficacy of a potent novel antimicrobial protein of mass 6 kDa, epidermicin NI01, for eradicating the nasal burden of MRSA in a cotton rat ( Sigmodon hispidus ) model. Methods: MRSA strain ATCC 43300 was used to establish a robust colonization of cotton rat nares. This model was used to evaluate the efficacy of topical 0.04% and 0.2% epidermicin NI01, administered twice daily for 3 days consecutively, and topical 0.8% epidermicin NI01 administered once, for reducing nasal MRSA burden. Control groups remained untreated or were administered vehicle only (0.5% hydroxypropylmethylcellulose) or 2% mupirocin twice daily for 3 days. The experiment was terminated at day 5 and MRSA quantitative counts were determined. Tissues recovered from animals treated with 0.2% epidermicin twice daily for 3 days were examined for histological changes. Results: Mupirocin treatment resulted in a reduction in burden of log10 (log R) of 2.59 cfu/nares compared with vehicle ( P  < 0.0001). Epidermicin NI01 administered once at 0.8% showed excellent efficacy, resulting in a log R of 2.10 cfu/nares ( P  = 0.0004), which was equivalent to mupirocin. Epidermicin NI01 administered at 0.2% or 0.04% twice daily for 3 days did not have a significant impact on the tissue burden recovered from the nares. Mild to marked histological abnormalities were noted, but these were determined to be reversible. Conclusion: A single dose of topical epidermicin NI01 was as effective as mupirocin administered twice daily for 3 days in eradication of MRSA from the nares of cotton rats. This justifies further development of epidermicin for this indication.